Preparation of lipophilic graphene oxide derivates via a concise route and its mechanical reinforcement in thermoplastic polyurethane. (6th October 2016) - Zhang, Yanbing; Liu, Luqi; Sun, Bing; Wang, Guorui; Zhang, Zhong
Abstract: A facile, effective and environmental friendly route was presented to prepare lipophilic graphene oxide (GO) derivates via the esterification reaction of the carboxylate salt of GO and 1-bromohexadecane in the presence of a phase-transfer reagent in water. The resultant long alkyl chains modified graphene oxide sheets (GO-HD) show the long-term and stable dispersion capability in many organic solvents. Successful grafting of long alkyl chains onto GO surfaces was confirmed through FTIR, XPS, TGA, UV–vis spectrum techniques. Moreover, we utilized the GO-HD as a reinforcing filler to prepare GO-HD/thermoplastic polyurethane (TPU) nanocomposites through solution casting method. The uniform distribution and good interfacial adhesion are expected for the GO-HD based nanocomposites due to the good compatibility between long alkyl chains of GO-HD fillers and TPU chains. Notably, tensile mechanical tests demonstrated that the GO-HD/TPU nanocomposites at low filler contents (≤2 wt%) exhibit higher modulus, ultimate tensile strength without compromising the intrinsic extensibility of TPU matrix as compared with the GO/TPU nanocomposites with same filler content. Further, in situ tensile-micro Raman spectroscopy tests were employed to monitor the load transfer process at a microscopic level, and revealed the improved load transfer efficiency in the GO-HD/TPU nanocomposites.